1976
DOI: 10.1002/1097-4679(197601)32:1<154::aid-jclp2270320139>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a marathon group on self-actualization and attitudes toward women

Abstract: This study investigated the impact of a 16-hour marathon session on levels of self-actualization and attitudes toward women both 1 day and 5 weeks after the group experience. Female undergraduates were assigned randomly to one of two marathon groups or to a no-treatment control group. Ss in both marathon groups experienced a significant shift toward increased independence or self-supportedness on both posttests. However, a differential group effect was found from separate comparisons of each marathon group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In the literature, the studies conducted on the impact of psychodrama on self-actualization reported contrasting findings. Certain study findings demonstrated that psychodrama was effective on self-actualization (Kilmann, Follinstad, Price, Rowland, and Robinson, 1976) and certain others reported that it was not (Rosenthal, 1976). In the present study, the findings suggested that the impact of psychodrama on self-realization was partly due to the fact that the participants could implement the awareness during both group and protagonist plays in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the studies conducted on the impact of psychodrama on self-actualization reported contrasting findings. Certain study findings demonstrated that psychodrama was effective on self-actualization (Kilmann, Follinstad, Price, Rowland, and Robinson, 1976) and certain others reported that it was not (Rosenthal, 1976). In the present study, the findings suggested that the impact of psychodrama on self-realization was partly due to the fact that the participants could implement the awareness during both group and protagonist plays in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Kilmann, Follingstad, Price, Rowland, and Robinson (1976) obtained global indexes of self-actualization by using only the two main scales of the POI that include all the items (Innerdirectedness and Time Competence). Two days after a 16-hour marathon, female undergraduate participants showed significant gains on the Innerdirectedness scale, whereas the scores of the members of the control group remained relatively unchanged.…”
Section: Self-actualizationmentioning
confidence: 99%
“…Two investigators (Livingston, 1972;Lunceford, 1974) held a black awareness encounter for black participants. Kilmann, Follingstad, Price, Rowland, and Robinson (1976) focused on the interpersonal roles of women. Nine studies conducted comparisons of different treatment methods (Bailey, 1974;Findley, 1974;Goodstein, 1972;Kilmann, 1973;Kilmann et al, 1975;Lewis, 1967;Mohr, 1970;O'Donnell, 1973;Weigel, 1968).…”
Section: Treatmentmentioning
confidence: 99%